EXPRESSION OF MODIFIED RECOMBINANT HUMAN ERYTHROPOIETIN IN CHO-K1 CELLS AND ITS IN VITRO PROLIFERATION ASSAY IN TF-1 CELLS - Adi Santoso (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Erythropoietin (EPO) is a 30 kDa glycoprotein hormone which is important for red blood cells maturation. EPO consists of 165 amino acids and possesses 3N-linked carbohydrate chains. Recombinant human erythropoietin (rHuEPO), such as epoetin-α and epoetin-β, have been used for many years to treat anemia in patients with chronic renal failure, systolic heart failure, HIV-AIDS, or cancer. In vivo stability of rHuEPOs were low due to rapid metabolisms by galactosyl receptor of the hepatocytes. Previously, a novel erythropoiesis stimulating protein (NESP) called darbapoetin-α (DARB) which possesses two additional N-linked glycosylation had been studied. It was observed that NESP showed better in vivo stability and biological activity compared to the unmodified form (containing only 3N-linked carbohydrate chains). Based on the above study, we attempted to synthesize recombinant human EPO (rHuEPO) by generating CHO-K1 cell lines expressing codon-optimized human epo open reading frame (ORF) in CHO-K1 cells. The ORF was modified to contain 5 N-linked carbohydrate chains. The media obtained from CHO-K1 cell culture was collected and diafiltrated with the use of tangential flow filtration. The rHuEPO protein containing polyhistidine tag was purified using affinity chromatography. An SDS/PAGE and Western blotting analyses confirmed that the purified protein was the modified rHuEPO. MTT based proliferation assay was conducted in TF-1 bone marrow cell line as a model. The result showed that the modified rHuEPO was able to enhance TF-1 cells proliferation.Key words: CHO-K1, erythropoietin, glycosylation, MTT assay and TF-1 cell line.